Predictors of At-Home Arterial Oxygen Desaturation Events in Ambulatory Surgical Patients. Issue 3 (April 2021) - Biddle, Chuck; Elam, Charles; Lahaye, Laura; Kerr, Gordon; Chubb, Laura; Verhulst, Brad
Abstract : Objectives: Little is known about the early recovery phase occurring at-home after anesthesia and surgery in ambulatory surgical patients. We studied quantitative oximetry and quality-of-life metrics in the first 48 hours after same-day orthopedic surgery examining the association between the recovery metrics and specific patient and procedural factors. Methods: We used the STOP-Bang score to quantify patient risk for obstructive sleep apnea in 50 adult patients at 2 centers using continuous portable oximetry and patient journaling. Parametric statistical procedures were used to assess relationships among patient and procedural factors and desaturation events. Results: Higher STOP-Bang scores were predictive of the number and duration of desaturation events below mild and severe thresholds for arterial oxygen saturation during their first 48 hours after discharge from ambulatory surgery. Older patients and patients with higher BMI in particular were at an increased risk of mild and severe arterial oxygen desaturation. Using a home CPAP reduced the number of desaturation events. Of interest, taking opiate analgesics decreased the number of desaturation events. Conclusions: Given the absence of systematic research of early ambulatory anesthesia/surgery recovery at home and concerns of postoperative respiratory events, our results have clear implications for patient safety. Our results imply that screening based on noninvasive STOP-Bang scores may allow for suggestions for recovery from ambulatory surgery, such as encouraging patients with high scores to use home CPAP and aggressive education regarding use of opiates. Abstract : Supplemental digital content is available in the text.